Removal of COD & NH3 from Produced Water using Modified Horizontal Subsurface Flow Constructed Wetlands (HSCW) - Agus Jatnika Effendi; Regi Risman Sandi (Reaktor, 2018)
It is very common that COD and NH3 are found in Produced Water with elevated concentration. One proven technology that is capable in removing organic substances and nutrients, is Horizontal Subsurface Flow Constructed Wetland (HSCW). Based on characterization of produced water from one oil field in Indonesia, it was shown that COD and NH3 were found to exceed the threshold limit stated in Ministry of Environmental Decree no. 19 Year 2010. Modified HSCWs were developed in order to treat produced water containing high concentration of COD and NH3 and allowing anaerobic process to occur in the reactor. The HSCWs were planted by three different species; they were Sagittaria palaefolia (Jasmine Water), Scirpus grossus (Mensiang), and Typha latifolia (Walingi). Organic loading rates (OLRs) to the HSCWs reactor were varied from 7.2 to 72 gr COD/m2.day. It was found that HSCW planted with Typha latifolia had the highest removal efficiency for both COD and NH3 when the OLR was set at 14.4 gr COD/m2.day. Anaerobic bacteria were found in high number indicating that these bacteria involved actively in removing pollutants containing in produced water. However, further microbiology study should be performed in order to determine the role of anaerobic bacteria.